Nanostructured biocomposite films of high toughness based on native chitin nanofibers and chitosan - Mushi, Ngesa E.; Utsel, Simon; Berglund, Lars A. (Frontiers in Chemistry, 2014)
Chitosan is widely used in films for packaging applications. Chitosan reinforcement by stiff particles or fibers is usually obtained at the expense of lowered ductility and toughness. Here, chitosan film reinforcement by a new type of native chitin nanofibers is reported. Films are prepared by casting from colloidal suspensions of chitin in dissolved chitosan. The nanocomposite films are chitin nanofiber networks in chitosan matrix. Characterization is carried out by dynamic light scattering, quartz crystal microbalance, field emission scanning electron microscopy, tensile tests and dynamic mechanical analysis. The nanostructured biocomposite was produced in volume fractions of 0, 8, 22 and 56% chitin nanofibers. Favorable chitin-chitosan synergy for colloidal dispersion is demonstrated. Also, lowered moisture sorption is observed for the composites, probably due to the favorable chitin-chitosan interface. The highest toughness (area under stress-strain curve) was observed at 8 vol% chitin content. The toughening mechanisms and the need for well-dispersed chitin nanofibers is discussed. Finally, desired structural characteristics of ductile chitin biocomposites are discussed.